Effects of Amplification Facilitators on Diagnostic PCR in the Presence of Blood, Feces, and Meat - Abu Al-Soud, Waleed (American Society for Microbiology, 2000)
The full potential of diagnostic PCR is limited, in part, by the presence of inhibitors in complex biological samples that reduce the amplification efficiency. Therefore, different pre-PCR treatments are being used to reduce the effects of PCR inhibitors. The aim of the present study was to investigate the effects of 16 amplification facilitators to enhance DNA amplification in the presence of blood, feces, or meat. Different concentrations of amplification facilitators and inhibitory samples were added to PCR mixtures containing rTth or Taq DNA polymerase. The addition of 0.6% (wt/vol) bovine serum albumin to reaction mixtures containing Taq DNA polymerase reduced the inhibitory effect of blood and allowed DNA amplification in the presence of 2% instead of 0.2% (vol/vol) blood. Furthermore, the addition of bovine serum albumin (BSA) to reaction mixtures containing feces or meat enhanced the amplification capacities of both polymerases. Taq DNA polymerase was able to amplify DNA in the presence of 4% instead of 0.4% (vol/vol) feces and 4% instead of 0.2% (vol/vol) meat, and rTth was able to amplify DNA in the presence of 4% instead of 0.4% (vol/vol) feces and 20% instead of 2% (vol/vol) meat. The single-stranded DNA binding T4 gene 32 protein (gp32) had a relieving effect similar to that of BSA, except when it was added to PCR mixtures of rTth containing meat and of Taq DNA polymerase containing feces. The relieving effects of betaine and a cocktail of proteinase inhibitors were more sample specific. The addition of 11.7% (wt/vol) betaine allowed Taq DNA polymerase to amplify DNA in the presence of 2% (vol/vol) blood, while the addition of proteinase inhibitors allowed DNA amplification by both polymerases in the presence of 4% (vol/vol) feces. When various combinations of betaine, BSA, gp32, and proteinase inhibitors were tested, no synergistic or additive effects were observed. The effects of facilitators on real-time DNA synthesis instead of conventional PCR were also studied.